Sosialisasi Dan Penguatan Kapasitas Kebijakan Desa Dalam Pencegahan Kekerasan Seksual Pada Anak - Karmila Damariani Radjak; Gito Alan Ali (AIWADTHU: Jurnal Pengabdian Hukum, 2023)
Introduction: Violence against children is any act against a child which results in physical, psychological, sexual misery or suffering, and/or neglect, including threats to commit acts, coercion, or deprivation of liberty by means against the law.Purposes of Devotion: This activity aims to integrate the Child Protection Program from Sexual violence into the policies of Mebongo Village, Sumalata District; Align the Village Child Protection Program from Sexual violence with Village policies in Sumalata District; Encourage the participation of all community groups in preventing and handling sexual violence against children. Method of Devotion: The form of the program is Socialization and Capacity Strengthening of Village Policies in order to realize Child Protection which provides justice and a sense of security that is needed and also to increase participation and a sense of shared responsibility in society, so that it can contribute to related institutional roles primarily at the village government level.Results of the Devotion: From the results of discussions with the community, it was obtained that the majority acknowledged the lack of education regarding good patterns of handling sexual violence, which refers to steps taken to identify, help, and protect children who are victims of violence, including access to justice for child victims and perpetrators. . This effort is carried out through networking (including advocacy) with affordable and quality support services for victims, perpetrators and children at risk. Then on the regulatory side, the Village does not yet have supporting facilities related to regulations that protect the rights of children who experience sexual violence